Activatable superparamagnetic iron oxide nanoparticles scavenge reactive oxygen species in macrophages and endothelial cells. Issue 68 (12th November 2020) - Nwasike, Chukwuazam; Yoo, Eunsoo; Purr, Erin; Doiron, Amber L.
Abstract : Complexed IPC-SPIOs scavenge intracellular ROS after internalization. Abstract : Reactive oxygen species (ROS) are key markers of inflammation, with varying levels of superoxide indicating the degree of inflammation. Inflammatory diseases remain the leading cause of death in the developed world. Previously, we showed that interpolymer complexed superparamagnetic iron oxide nanoparticles (IPC-SPIOs) are capable of decomplexing and activating T2 magnetic resonance (MR) contrast in superoxide-rich environments. Here, we investigate the ability of IPC-SPIOs to scavenge ROS in immune and endothelial cells which should activate the superparamagnetic core. In exogenously generated superoxide, ROS scavenging by the nanoparticles was concentration dependent and ranged from 5% to over 50% of available ROS. A statistically significant reduction in ROS was observed in the presence of IPCSPIOs compared to poly(ethylene glycol)-coated SPIOs (PEG-SPIOs). During in vitro cellular assays, a reduction in ROS was observed in macrophages, monocytes, and human endothelial cells. Macrophages and endothelial cells experienced significantly higher ROS reduction compared to monocytes. ROS scavenging peaked 12 hours post-exposure to IPC-SPIOs in most studies, with some cell samples experiencing extended scavenging with increasing IPC-SPIO concentration. At the tested concentrations, particles were not cytotoxic, and confocal imaging showed localization of particles within cells. These findings demonstrate the potential of IPC-SPIOs as activatable MR contrast agents capable of activating under inflammation-induced cellular redox conditions as reporters of inflammatory disease severity or staging.